A cellular 65-kDa protein recognizes the negative regulatory element of human papillomavirus late mRNA - Dietrich-Goetz, Walter (National Academy of Sciences, 1997)
Papillomavirus late gene expression is tightly linked to the differentiation state of the host cell. Levels of late mRNAs are only in part controlled by regulation of the late promoter, other posttranscriptional mechanisms exist that reduce the amount of late mRNA in undifferentiated cells. Previously we described a negative regulatory element (NRE) located upstream of the human papillomavirus type 16 late poly(A) site. We have delineated the NRE to a 79-nt region in which a G+U-rich region was the major determinant of NRE activity. UV-crosslinking assays identified a prominent nuclear protein of 65 kDa as the only factor in close contact with the NRE, and a complex of at least five proteins, including the 65-kDa protein, was enriched on NRE–RNA. Binding of the 65-kDa protein was depleted by preincubation with poly(U) Sepharose in high salt, a property characteristic of the U2 small nuclear ribonucleoprotein auxiliary factor U2AF(65) and bacterially expressed U2AF(65) exhibited NRE binding. The 65-kDa protein bound to the G+U-rich NRE 3′ half which shows homology to the B2P2 sequence a known U2AF(65) binding site in the α-tropomyosin gene, and the G+U-rich element can be replaced by B2P2 in the binding assay. Treatment of cells with phorbol 12-myristate 13-acetate reduced binding of the 65-kDa protein, induced NRE binding of a cytoplasmic protein, and relieved the NRE block on reporter gene expression.